PEMBAGIAN DAN PEMANFAATAN HASIL LUBUK LARANGAN PADA TRADISI MANCOKAU IKAN LUBUK LARANGAN di DESA TANJUNG BELIT KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR - Rechika Ferlania; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted in Tanjung Belit Village. The purpose of this study is to find out how the distribution system of fish from the results of fish maneuvers in the Lubuk ban Tanjung Belit Village, and to find out how to use the results of fish maneuvers under the prohibition. In determining the subject of research using purposive sampling techniques that have been determined based criteria. This study uses qualitative research methods with data collection techniques by conducting interviews and documentation. The number of informants in this study amounted to 8 people. The theory used is Social Systems Theory. The results of this research that is the tradition of catch fishing in river ban is an annual activity of the Tanjung Belit village community which is carried out once a year. This tradition in the form of community activities to catch fish together at the bottom of the ban and the fish will be sold by auction and andel distribution systems. There are two types of andel division namely the inner and outer andel. This tradition is the local wisdom of the Tanjung Belit people who originally intended to raise funds to build the village and also to preserve the Subayang River to keep it awake and not be polluted. Keywords: Tradition, River Ban, Mancokau